A tool for distributed collaborative electromagnetic transients studies allowing on-demand interaction. (September 2022) - Gomes, J.P.R.; Boaventura, W.C.
Highlights: Implementation of a distributed computational platform for collaborative work in the calculation of electromagnetic transients. Performing simulations for large systems integrating smaller subsystems. Distributed computing using separate computers (inside - or not - a LAN – Local Area Network) connected using internet protocols. Performing electromagnetic transients calculation using geographically dispersed computers. Conducting simulations within a subsystem with complete privacy, caring for intellectual property issues. Abstract: This work presents a computational architecture tool aimed to provide a distributed and collaborative environment for electromagnetic transients calculations. Through this tool, different systems, running on different computers in distributed locations, can connect using internet protocols to form large systems. Innovatively, it allows the integration between the subsystems to occur on-demand, which differentiates it from the existing proposals in the literature. Also, it allows user interaction with the power system during the simulation. Such features are demonstrated by means of case studies running on the tool on-demand mode of operation. The opportunities arisen from the tool are further presented using a case study for large systems, 3200 buses, 28 wind farms and 7 solar farms, and also using smaller subsystems, 39 Bus. The results comprise the simulations total running time, a brief discussion about the computers communication latency and the benefits through collaborative work the tool adds to the field of electromagnetic transients calculation.